2019
DOI: 10.35869/vial.v0i16.92
|View full text |Cite
|
Sign up to set email alerts
|

Readability indices for the assessment of textbooks: a feasibility study in the context of EFL

Abstract: Readability indices have been widely used in order to measure textual difficulty. They can be useful for the automatic classification of texts, especially in language teaching. Among other applications, they allow for the previous determination of the difficulty level of texts without the need of reading them through. The aim of this research is twofold: first, to examine the degree of accuracy of the six most commonly used readability indices, and second, to present a new optimized measure. The main problem i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
1
0
2
Order By: Relevance
“…Each observes texts differently yet has the same goal: calculating a text's readability. Therefore, it can be concluded that the measurement of the texts in English for Nusantara is valid as there is still a debate on the validity of readability level when using only one readability formula, particularly its validity aspect (Gómez & Sánchez-Lafuente, 2019). The fact that the texts are measured using formulas intended to measure texts' readability ensures the measurement's validity.…”
Section: The Level Of Readability Of English For Nusantara Based On T...mentioning
confidence: 99%
“…Each observes texts differently yet has the same goal: calculating a text's readability. Therefore, it can be concluded that the measurement of the texts in English for Nusantara is valid as there is still a debate on the validity of readability level when using only one readability formula, particularly its validity aspect (Gómez & Sánchez-Lafuente, 2019). The fact that the texts are measured using formulas intended to measure texts' readability ensures the measurement's validity.…”
Section: The Level Of Readability Of English For Nusantara Based On T...mentioning
confidence: 99%
“…Bu tahmin en pratik ve daha az zaman alan yol olarak kabul edilen ve metinlerin göreceli zorluğunu nesnel olarak ölçmeyi amaçlayan istatistiksel araçlar olarak görülen (Klare, 1963) çeşitli formüller vasıtasıyla yapılır. Yabancı dil olarak İngilizce öğretimi açısından bu formüller genellikle okuyucunun kavrayışını metnin dilsel özellikleriyle ilişkilendirmeye çalışan, metinlerin zorluk düzeylerinin belirlenerek öğrenci seviyesine göre sınıflandırılması amacıyla kullanılan matematiksel denklemlerdir (Danielson, 1987;Gomez & Sanchez-Lafuente, 2019).…”
Section: Introductionunclassified
“…Okunabilirlik açısından zor olan metinler yabancı dil olarak İngilizce öğretiminde özellikle de okuduğunu anlamada öğrenci başarısını etkileyen faktörlerden biridir. (Gomez & Sanchez-Lafuente, 2019;Kuterovac, 2016;Zamanian & Heydari 2012). Bu bağlamda ortaöğretim İngilizce ders kitaplarındaki metinlerin zorluk düzeylerinin tespit edilmesinin, metinlerin öğrenci seviyesine uygun bir şekilde sınıflandırılması ve düzenlenmesine neden olarak öğrenci başarısının artmasına da katkı sağlayacağı düşünülmektedir.…”
Section: Introductionunclassified